Design of Palm Seeds Sorting Machine. Issue 1 (July 2020) - Tamrin, T; Lanya, Budianto; Warji, W; Nasrullah, N
Abstract: The need for oil palm seeds in Indonesia has increased lately. Palm seeds can be grown from the kernel. To get a uniform size kernel requires uniform size seeds. This study aims to design, make a separator of palm seeds so that the size of the uniform seeds. The design phase did using a CAD program to draw engineering drawings. Based on engineering drawings, we analyzed and made prototypes of palm seed sorting machines. The size of the prototype was 182 cm long, 50 cm wide and 94 cm high. This machine sorted seeds into large, medium and small dimensions The test results of 300 seeds consisting of 100 large size seeds, 100 medium size seeds and 100 small size seeds, produced 29.5% large size, 30.8% small size 28.2% small size. The capacity of the machine was 60, 2 kg per hour. The palm oil seed sorting machine has an optimum percentage of 88.87%.